Top‐down and bottom‐up: Examining reciprocal relationships between leader humility and team helping behavior - Wang, Danni; Liu, Yuwen; Hsieh, Ying‐Che; Zhang, Zhen (Journal of organizational behavior, 2022)
Summary Based on social exchange theory, we develop and test a longitudinal model in which leaders' expressed humility and team members' helping behavior reciprocally influence each other over time and ultimately predict subsequent team performance and turnover. Using multisource, 3‐wave repeated measures data from 281 work teams, our cross‐lagged panel modeling results supported the hypotheses. We found that leader humility increased subsequent team helping behavior, and team helping behavior also promoted leader humility at a later time. As compared with leader humility, team helping behavior is a more proximal predictor of team performance and reduced team turnover rate. We found that leader humility has indirect effects on team performance and team turnover through the mediating role of team helping behavior. These findings shed new light on how leaders and teams can develop through their respective humble and helping behaviors, and how this reciprocal relationship ultimately enhances team effectiveness and helps reduce turnover of team members.